(untitled) - Graedon, Joe (New York, 1996)
Topics covered include new warnings about side effects and interactions. Breakthroughs that could change your life. How, when and with what to take your medications. New drugs such as Imitrex, Effexor, Aleve, Pepcid AC, Tagament HB, and Zantac 75: what they do and what to watch out for home remedies for arthritis, dandruff, hiccups, heartburn, bug bites, bad breath, and more. Drugs for children and women (including the latest word on Ritalin estrogen treatment, and contraceptives) Ready-reference guide to the 100 most commonly prescribed drugs
Keywords: Thuốc,Drugs; Tác dụng phụ,Side effects